Pemetaan dan Perancangan Perbaikan Proses Produksi untuk Persiapan Industri 4.0 di PT. X - Kevin Purnomo (Jurnal Titra, 2019)
PT. X is a manufacturing company produces circuit breaker products. PT. X needs to prepare the development based on the industri 4.0 era. The purpose of this research is mapping and evaluate each department to find out activities that have not and have applied the principle of industrial system 4.0, and make preparations improvements based on framework industry 4.0. The results of mapping and evaluation indicate there are five departments classified "Few Implemented Industry 4.0", three departments classified "Partially Implemented Industry 4.0", and three departments classified "fully implemented industry 4.0". Proposed problem solution carried out for MPO and MH departments process production activites. Delivering material documents problem, inaccurate data request material, and finished good shipments to Warehouse are the problems that will be analyzed. Improving the system delivery of material documents changed to digitalization, which before done manually sent the documents, changed using e-mail. The financial savings obtained from proposed solution is Rp. 14,440,373 per year. Improvements also made for the delivery finished good problem, by analyzing the percentage productivity workers with work sampling method that showed 93%. The proposed solution in the delivery finished good was changed with AGV, providing financial savings until Rp. 1,005,633.00 per year per production segment.